Digital transformation: Some implications for financial and macroeconomic stability - Hans Genberg (Asian Development Bank Institute (ADBI), 2020)
Digital transformation is changing how and by whom financial services are provided, how payments are made within an economy and across borders, and how and where goods and services are produced in a globalized economy. These transformations bring significant benefits in the form of greater variety and convenience of financial services, faster speed of payment transactions, and more efficient production processes. But there are also potential costs. Traditional commercial banking models are challenged by unregulated FinTech and BigTech firms, possibly threatening systemic financial stability. Globalization of production processes has led to greater spillovers of economic fluctuations across borders, thereby complicating macroeconomic policy decisions. This paper reviews how digital transformation is likely to impact financial stability, payment systems, and macroeconomic stability, and discusses the need for changes in regulatory and macroeconomic policies to mitigate the associated risks. The paper ends with reflections on the possible consequences of the current Coronavirus pandemic for the analysis and conclusions.
Keywords: E31; F62; G21; G22; 330; digital transformation; financial intermediation; FinTech; BigTech; global value chains